A taxonomy of logistics centres: overcoming conceptual ambiguity. Issue 3 (4th May 2017) - Notteboom, Theo; Parola, Francesco; Satta, Giovanni; Risitano, Marcello
ABSTRACT: This manuscript aims to disentangle the conceptual ambiguity around the notion of logistics centre. It proposes an overarching framework that categorises different types of infrastructure and identifies their distinctive components. The lack of a sound conceptualisation of logistics centres originates from the variety in temporal and spatial approaches. In transportation chains, path-breaking trends in market needs, technological innovations and institutional changes, as well as the place specificity of logistics centres embedded in various national contexts, inevitably led to a substantial theoretical ambiguity. This study consolidates prior fragmented works and identifies suitable criteria for classifying logistics centres. The functional criterion is proposed as a cornerstone for building a sound conceptualisation of these infrastructures. By capturing the distinctive characteristics of each type of logistics centre, the paper proposes an original and comprehensive taxonomy, which emphasises commonalities and specificities of various infrastructures. The paper provides a contribution to literature by sketching out a trustworthy conceptualisation of logistics centres. In addition, the outcomes bring insightful implications for researchers, policy-makers and practitioners.